Development of a new class of brominated polymeric flame retardants based on copolymers of styrene and polybutadiene - Beach, Mark W.; Hull, John W.; King, Bruce A.; Beulich, Inken I.; Stobby, Bill G.; Kram, Shari L.; Gorman, Dave B. (Polymer degradation and stability, 2017)
Brominated polymeric flame retardants (FR) have been developed that can provide effective flame retardant performance in polymer systems that previously relied on hexabromocyclododecane (HBCD). This polymeric FR material exhibits a superior environmental profile to that of HBCD and other lower molecular weight FR molecules. The brominated polymer flame retardant is based on a copolymer of styrene and butadiene where the polybutadiene portion is brominated on the 1,2 and 1,4 isomer units to give a brominated polybutadiene. Bromination is best carried out with a quaternary ammonium tribromide reagent which provides a selective bromination of just the polybutadiene portion of the copolymer. A styrene-butadiene-styrene (SBS) triblock architecture is utilized where the presence of the styrene enhances the thermal stability and gives the copolymer to better compatibility when blended with polystyrene. The resulting brominated polybutadiene-polystyrene (BrPBPS) polymeric flame retardant contains similar aliphatic bromine as in HBCD but with a higher molecular weight structure. BrPBPS provides similar flame retardant activity as HBCD in polystyrene blends where both release HBr to provide gas phase activity. Both also provide enhanced polymer degradation as another major pathway for condensed FR activity.